Importance of the international accreditation of medical schools - Valdivieso Rodriguez, Manuel (2023)
As of 2024, medical school graduates who wish to pursue graduate studies in the U.S. or in Canada, they must have graduated from medical schools with quality educational programs endorsed by recognized agencies, capable of granting international accreditation.   The World Federation for Medical Education (WFME) is one of these agencies.  The WFME accepted the new accreditation policy of the Educational Committee for Foreign Medical Education (ECFMG) whereby physicians applying for ECFMG certification from 2024 onwards, must have graduated from a university medical center accredited by a quality assurance agency that is recognized by the WFME. The COMAEM (Mexican Council for the Accreditation of Medical Education) is endorsed by the WFME and other international organizations that ensure the quality of higher education. The accreditation granted by COMAEM is a recognition that the medical program meets the criteria, indicators and quality parameters established by this organization. Starting in 2024, graduates of an accredited program will be able to apply for ECFMG certification through the United States Medical Licensing Examination (USMLE) and thus be able to do a specialty residency or work in the U.S.  In Peru, only the Alberto Hurtado School of Medicine of the Cayetano Heredia Peruvian University has completed the international accreditation process through COMAEM and has received such accreditation.